1998
DOI: 10.4148/1090-7025.1006
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Silver, Zinc-Palladium, and Zinc-Gold as Bimetallic Systems for Carbon Tetrachloride Dechlorination in Water

Abstract: Doping of zinc with silver, palladium, and gold was found to increase reactivity towards carbon tetrachloride in water. Commercial zinc dust, cryochemically prepared zinc metal particles (SMAD nanoparticles), and zinc dust pressed into pellets (mechanically activated zinc) were employed. Reduction products detected were methane, ethylene, acetylene, and other hydrocarbons along with products of partial dechlorination such as chloroform, methylene chloride, and methyl chloride. Dichloroethylenes (DCEs) and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…An important contribution to this field was done by Boronina et al, who demonstrated that metallic zinc is an ideal candidate for the practical destruction of carbon tetrachloride in water . In a preliminary work, zinc dust was reported to cause deep sequential dechlorination of carbon tetrachloride to give methane as the main final organic product, chloroform, methylene chloride, and methyl chloride being intermediate reaction compounds 472a.…”
Section: Group Iib:  Znmentioning
confidence: 99%
See 1 more Smart Citation
“…An important contribution to this field was done by Boronina et al, who demonstrated that metallic zinc is an ideal candidate for the practical destruction of carbon tetrachloride in water . In a preliminary work, zinc dust was reported to cause deep sequential dechlorination of carbon tetrachloride to give methane as the main final organic product, chloroform, methylene chloride, and methyl chloride being intermediate reaction compounds 472a.…”
Section: Group Iib:  Znmentioning
confidence: 99%
“…An important contribution to this field was done by Boronina et al, who demonstrated that metallic zinc is an ideal candidate for the practical destruction of carbon tetrachloride in water . In a preliminary work, zinc dust was reported to cause deep sequential dechlorination of carbon tetrachloride to give methane as the main final organic product, chloroform, methylene chloride, and methyl chloride being intermediate reaction compounds 472a. In general, superior and different behavior was observed for zinc in comparison with magnesium or tin, the most active samples being prepared by a metal vapor−solvent co-deposition method (cryoparticles) or by mechanical treatment. 472a-e Doping zinc with silver, palladium, or gold resulted in a 4−10-fold increase in the carbon tetrachloride degradation rate and conversion to methane 472f.…”
Section: Group Iib:  Znmentioning
confidence: 99%
“…12 The drawbacks of this technique include the rate of reaction, the selectivity of the reaction and the poisoning of electrode surfaces. 16,17 The following series of reactions is considered to represent a reasonable mechanistic scheme that can account for the liberation of EDTA and the removal of copper, iron and manganese from aqueous media by cementation and/or precipitation. 13 The use of zero-valent metals has been investigated 14,15 as a mean of removing metal ions from aqueous streams by cementation/precipitation.…”
Section: Reprintsmentioning
confidence: 99%
“…Zerovalent zinc (ZVZn) has also been evaluated for treating organics-contaminated waters ( ). This metal is more thermodynamically active and reactive than iron.…”
Section: Introductionmentioning
confidence: 99%
“…This metal is more thermodynamically active and reactive than iron. Experi ments conducted to examine the degradation of chlorinated solvents using zerovalent zinc have shown faster degradation kinetics compared to iron ( ). This metal has not been used for the degradation of nitroaromatic compounds in environmental media.…”
Section: Introductionmentioning
confidence: 99%